The implementation of obstruction of justice concept in Indonesia legal system / Widati Wulandari and Nella Sumika Putri - Wulandari, Widati; Sumika Putri, Nella (2014)
Indonesia, as a state party of UNCAC (Law No. 7 Year 2006) and Palermo Convention (Law No. 5 Year 2009) about Transnational Organized Crime, has obligation to create Implementing Legislation through municipal Law. One of the aspect that shall be regulated in the Implementing Legislation is the Obstruction of Justice which is a new concept for Indonesia legal system. As the new concept, the Obstruction of Justice has not been completely implemented in Indonesia Legal System. For example, Indonesia has legislation that regulated in general an act to interfere in the giving of testimony or to induce false testimony but there is no clear legislation that regulated the protection for the Law Enforcement officer from intimidation or interfere their official duties as specified in the Obstruction of Justice Concept. Moreover, the Obstruction of Justice in Indonesia legal system has not been regulated in one specified Legislation but it is spreaded inside and outside Indonesian Penal Code.Therefore, to gain full understand about the concept and how to snychronize and harmonize the concept in Indonesia Legal system, this paper will describe the Obstruction of Justice Concept in accordance with the International convention and then compare its implementation in Indonesia with that other countries.